Perioperative Pain and Addiction Interdisciplinary Network (PAIN): consensus recommendations for perioperative management of cannabis and cannabinoid-based medicine users by a modified Delphi process. (January 2021) - Ladha, Karim S.; McLaren-Blades, Alexander; Goel, Akash; Buys, Michael J.; Farquhar-Smith, Paul; Haroutounian, Simon; Kotteeswaran, Yuvaraj; Kwofie, Kwesi; Le Foll, Bernard; Lightfoot, Nicholas J.; Loiselle, Joel; Mace, Hamish; et al.
Summary: In many countries, liberalisation of the legislation regulating the use of cannabis has outpaced rigorous scientific studies, and a growing number of patients presenting for surgery consume cannabis regularly. Research to date suggests that cannabis can impact perioperative outcomes. We present recommendations obtained using a modified Delphi method for the perioperative care of cannabis-using patients. A steering committee was formed and a review of medical literature with respect to perioperative cannabis use was conducted. This was followed by the recruitment of a panel of 17 experts on the care of cannabis-consuming patients. Panellists were blinded to each other's participation and were provided with rater forms exploring the appropriateness of specific perioperative care elements. The completed rater forms were analysed for consensus. The expert panel was then unblinded and met to discuss the rater form analyses. Draft recommendations were then created and returned to the expert panel for further comment. The draft recommendations were also sent to four independent reviewers (a surgeon, a nurse practitioner, and two patients). The collected feedback was used to finalise the recommendations. The major recommendations obtained included emphasising the importance of eliciting a history of cannabis use, quantifying it, and ensuring contact with a cannabis authoriser (if one exists). Recommendations also included the consideration of perioperative cannabis weaning, additional postoperative nausea and vomiting prophylaxis, and additional attention to monitoring and maintaining anaesthetic depth. Postoperative recommendations included anticipating increased postoperative analgesic requirements and maintaining vigilance for cannabis withdrawal syndrome.